2015
DOI: 10.1186/s12931-015-0278-3
|View full text |Cite
|
Sign up to set email alerts
|

BARD1 mediates TGF-β signaling in pulmonary fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a rapid progressive fibro-proliferative disorder with poor prognosis similar to lung cancer. The pathogenesis of IPF is uncertain, but loss of epithelial cells and fibroblast proliferation are thought to be central processes. Previous reports have shown that BARD1 expression is upregulated in response to hypoxia and associated with TGF-β signaling, both recognized factors driving lung fibrosis. Differentially spliced BARD1 isoforms, in particular BARD1β, are onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…Finally the deposition of ECM leads to the development of IPF [ 34 36 ]. TGF-β1 is thought to drive the cardinal processes to the initiation and progression of lung fibrosis, including inflammatory response, epithelial cell apoptosis, EMT, fibroblast proliferation, and collagen deposition [ 37 ]. In our model, the immunohistochemistry and western analysis shown the expression of TGF-β1 increased to varying degrees after baicalin administration to both WT and KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally the deposition of ECM leads to the development of IPF [ 34 36 ]. TGF-β1 is thought to drive the cardinal processes to the initiation and progression of lung fibrosis, including inflammatory response, epithelial cell apoptosis, EMT, fibroblast proliferation, and collagen deposition [ 37 ]. In our model, the immunohistochemistry and western analysis shown the expression of TGF-β1 increased to varying degrees after baicalin administration to both WT and KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study showed that TGF-β1 increases vascular cell adhesion molecule 1 and promotes fibroblast proliferation in IPF patients (147). Furthermore, TGF-β1 enhances fibroblast proliferation and promotes pulmonary fibrosis via BARD1 (BRCA1 Associated RING Domain 1) pathway (148).…”
Section: Tgf-βmentioning
confidence: 99%
“…Yang et al ( 29 ) reported that ZDHHC4, which causes a significant downregulation of circRNAhsa_circ_104310, is a significant methylation marker to regulate the expression of large groups of genes in a trans-acting manner in IPF. André et al ( 30 ) demonstrated that BRCA1-associated RING domain 1, the host gene of hsa_circRNA_102910, regulates lung epithelial cell damage and fibroblast proliferation by acting as a mediator of hypoxia and TGF-β may be a novel target for IPF treatment. hsa_circRNA_102348 is spliced from the elongator acetyltransferase complex subunit 2 gene, which encodes a general binding partner or chaperone for the activation and nuclear translocation of signal transducer and activator of transcription (STAT)3 ( 31 ) and may regulate the JAK/STAT signalling pathway.…”
Section: Discussionmentioning
confidence: 99%